MENUMBUHKAN EMPATI: KEKUATAN SASTRA UNTUK MEMBENTUK KESADARAN LINGKUNGAN - Zainal Abidin, Noor Azlinda; Nurul Fatwa Mohd Razali , Noraisah; Jariyah Hassan, Siti Ainun; Zahari , Hamizah (Global Synthesis in Education Journal, 2025)
The practice of using learning management systems has been fully implemented during the pandemic and it has been shifted to the post-pandemic era. As the government encourages blended learning, it is now a compulsory requirement during the post-pandemic era for instructors and students to use learning management systems.  This study explores the perception of language teachers or instructors on the use of LMS to teach English among tertiary level technical university students. Further investigation on different types of LMS such as Moodle, Google Classroom and MS Teams are also explored in this study.  It focuses on the following parameters; its user-friendly, instructions given, course requirements, assignment types, linguistic range or activity, and course administrator requirements. Data were collected from questionnaires and open-ended questions. In conclusion, this study emphasizes the diverse landscape of LMS platforms used by instructors, with university-provided systems, Google Classroom, and Edmodo being among the most popular choices. The study also highlights the importance of autonomy in LMS selection, with the majority of instructors having the freedom to choose their preferred platform. Overall, the results underscore the need for flexibility and efficiency in LMS adoption to cater to instructors' specific teaching needs while ensuring a streamlined learning experience for students